2021
DOI: 10.3389/fimmu.2020.612336
|View full text |Cite
|
Sign up to set email alerts
|

Gut Commensal-Induced IκBζ Expression in Dendritic Cells Influences the Th17 Response

Abstract: Intestinal commensal bacteria can have a large impact on the state of health and disease of the host. Regulation of Th17 cell development by gut commensals is known to contribute to their dichotomous role in promoting gut homeostasis and host defense, or development of autoimmune diseases. Yet, the underlying mechanisms remain to be fully elucidated. One candidate factor contributing to Th17 differentiation, and the expression of which could be influenced by commensals is the atypical nuclear IκB protein IκBζ.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Of interest, secretion of IL‐6 and IL‐10 in response to infection was found to be dependent on IκBζ in BMDCs. This study also showed that the commensals stimulate TLR4 signalling which in response stimulates the secretion of Th‐17‐inducing cytokines in BMDCs 93 . Moreover, IκBζ also upregulates Nlrp3 gene in bone marrow‐derived macrophages, thereby, playing crucial role in the activation of NLRP3 inflammasome 94 .…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Of interest, secretion of IL‐6 and IL‐10 in response to infection was found to be dependent on IκBζ in BMDCs. This study also showed that the commensals stimulate TLR4 signalling which in response stimulates the secretion of Th‐17‐inducing cytokines in BMDCs 93 . Moreover, IκBζ also upregulates Nlrp3 gene in bone marrow‐derived macrophages, thereby, playing crucial role in the activation of NLRP3 inflammasome 94 .…”
Section: Introductionmentioning
confidence: 56%
“…This study also showed that the commensals stimulate TLR4 signalling which in response stimulates the secretion of Th‐17‐inducing cytokines in BMDCs. 93 Moreover, IκBζ also upregulates Nlrp3 gene in bone marrow‐derived macrophages, thereby, playing crucial role in the activation of NLRP3 inflammasome. 94 Interestingly, the potential regulatory role of Nfkbiz in the skin immunity was exposed when Nfkbiz ‐deficient mice was found to spontaneously develop dermatitis along with expansion of Staphylococcus xylosus in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Ligand recognition mediates both internalization and signaling. Furthermore, DC-SIGN-dependent cross-presentation is enhanced by the simultaneous triggering of TLRs, being described as its ability to modify TLR signaling in a pro- or anti-inflammatory way depending on the ligand recognized. , …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DC-SIGN-dependent cross-presentation is enhanced by the simultaneous triggering of TLRs, being described as its ability to modify TLR signaling in a pro-or anti-inflammatory way depending on the ligand recognized. 44,45 The dual role in mediating both tolerance and immune response, depending on the context, might have been exploited by pathogens and tumors that upregulate the expression of DC-SIGN ligands to take advantage of DC-SIGN-dependent tolerogenic signaling as a strategy to escape the immune system. 18,44 DC-SIGN preferentially binds to fucosylated glycans, such as blood-type Lewis antigens (Le a , Le b , Le X , Le Y , and sulfo-Le a ) 46 stimulates the TLR-induced cytokine response.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Bacteroides have the capacity for immunomodulation, and their encoded bd oxidase renders their colonization of the intestine and positive alterations of the intestinal environment easier [ 54 ]. This microbial genus stimulates the differentiation of naïve CD4+ cells to Treg cells, increases IL-10 levels [ 62 ], and maintains the balance between Treg cells and proinflammatory Th17 and Th2 cells [ 63 ]. A reduction in the relative abundance of Bacteroides in the intestine triggers the onset of asthma [ 64 ].…”
Section: Discussionmentioning
confidence: 99%